If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + -3(x + 2) = -15 Reorder the terms: 9 + -3(2 + x) = -15 9 + (2 * -3 + x * -3) = -15 9 + (-6 + -3x) = -15 Combine like terms: 9 + -6 = 3 3 + -3x = -15 Solving 3 + -3x = -15 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -3x = -15 + -3 Combine like terms: 3 + -3 = 0 0 + -3x = -15 + -3 -3x = -15 + -3 Combine like terms: -15 + -3 = -18 -3x = -18 Divide each side by '-3'. x = 6 Simplifying x = 6
| (-4y)(7)= | | 7-4r=35 | | 5x^2+3x+2=x+6 | | 2x^2-7x+8=8 | | x^2+12x-582=0 | | -2(2x-4)=8(x+2) | | x^2-582=0 | | x^2+40x-84=0 | | 2y^2+4y+4=100 | | 15.16=3k-(-4.03) | | 2m-5m=42 | | x^5-4x^3+8x^2-32x=0 | | 4x+6x=9x^2-15x | | 10y+4=1y-8 | | 3m-5m=7 | | 5v-30=20 | | 35-(-t)=7 | | 35-(-t)=67 | | 6z-20=64 | | 15m+64=-7m+16 | | 15+-7y=-62 | | 12+5.75=5.87 | | 13x+13y+ax+ay=0 | | 17+12n=86 | | 0.35x=0.425 | | K^2-3k-40=0 | | -18.25+6.5y=66.25 | | -2(2x-4)=8x | | g-(-164)=489 | | f(2)=-3x+5 | | 1.2x=1.75 | | 8x^2-3y^2=0 |